Fe3O4@iron-based metal–organic framework nanocomposite [Fe3O4@MOF (Fe) NC] as a recyclable magnetic nano-organocatalyst for the environment-friendly synthesis of pyrano[2,3-d]pyrimidine derivatives - Hootifard, Ghader; Sheikhhosseini, Enayatollah; Ahmadi, Sayed Ali; Yahyazadehfar, Mahdieh (Frontiers in Chemistry, 2023)
Various pyrano[2,3-d]pyrimidines were synthesized by multicomponent reaction of aldehydes, malononitrile, and acidic C-H compounds such as barbituric acid through the tandem Knoevenagel–Michael cyclocondensation pathway in an environmentally friendly reactive medium in the presence of a recoverable nanocomposite. This nanocomposite includes Fe3O4 nanoparticles placed on an organometallic framework (Fe3O4@MOF(Fe)NC). The synthesized Fe3O4@iron-based metal organic framework nanocomposite nanocomposite (Fe3O4@MOF (Fe) NC) was characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectroscope (EDX), X-ray powder diffraction (XRD) and vibrating sample magnetometer (VSM) and thermogravimetric analysis (TGA).